Correlation Between Advertising Exposure of Traveloka and Level of Income with People Interest in Transact on Traveloka - Anugerah Dwitama; Djoko Setyabudi (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2018)
With total advertisement spend of Rp 687.7 billion throughout 2016, Traveloka has been very intent explaining the advantages and convenience of their sites and applications to the people of Indonesia. Therefore, Traveloka should be the main reference in the matter of booking airline tickets and hotel reservations in Indonesia. However, Traveloka has not succeeded in becoming the ultimate reference in the matter of reserving airline tickets or hotel reservations by the public. The purpose of this research is to know the correlation between advertising exposure of Traveloka and level of income with people interest in transact on Traveloka. The theory that used in this research is Advertising Exposure Theory and Theory of Social Category. This research is a quantitative research with explanatory type. This study uses people in Semarang who are 17-35 years old that has been exposed to advertising exposure of Traveloka and traveling out of town or overseas at least once a year. Based on the hypothesis test that conducted using Kendall’s Tau-b correlation analysis, shows that : First, there is a positive correlation between advertising exposure of Traveloka with people interest in transact on Traveloka with significance value 0,002 and correlation coefficient value 0,315. The higher advertising exposure of Traveloka, the higher people interest in transact on Traveloka, vice versa. Second, there is a positive correlation between level of income with people interest in transact on Traveloka with significance value 0,000 and correlation coefficiet 0,475. The higher level of income, the higher people interest in transact on Traveloka, vice versa. With these results, suggested to Traveloka to create ads with a variety of messages according to the desired segmentation, in order to reach the segmentation of potential travelers Traveloka in order to have interest to use Traveloka.